THE EFFECT OF ADDING CHICKEN EGGS SHELL FLOUR IN THE RATING ON THE CARCASES OF QUILLS AGED 6 WEEKS - ., Giovani; Wirapartha, M.; Umiarti, A.T. (Jurnal Peternakan Tropika, 2024)
This study was conducted to determine the effect of adding broiler egg shell flour to the carcass of six weeks old quail. It was held for 4 weeks at the Unud Pasraman Housing, Block F-30 and the Poultry Laboratory of the Faculty of Animal Husbandry, Udayana University, Bali. The study used a completely randomized design (CRD) with four treatments and four replications. The four treatments were: rations without the addition of broiler eggshell flour (P0), rations fed with 4% chicken eggshell flour (P1), rations fed with 6% chicken eggshell flour (P2), rations fed with flour chicken egg shells as much as 8% (P3). The variables observed were slaughter weight, carcass weight, carcass percentage, carcass composition. The results of this study showed that the slaughter weight of quail Coturnix-coturnix japonica which was given the addition of 4% (P1), 6% (P2), and 8% (P3) eggshell flour in the diet was significantly (P<0.05) higher than that of eggshell flour. control (P0). Carcass weight had a significant effect (P<0.05) compared to the control treatment (P0). The carcass percentage had a significant effect (P<0.05) compared to the control treatment (P0). Carcass physical composition (percentage of meat and fat) had a significant effect (P<0.05) compared to the control treatment (P0). The percentage of quail bones treated P1, P2, and P3 had no significant effect (P>0.05) with control P0. The conclusion of this study showed that giving broiler egg shell flour with concentrations of 4%, 6% and 8% in the ration could increase slaughter weight, carcass weight, carcass percentage, meat percentage, fat percentage but did not increase bone percentage in CoturnixCoturnix japonica 6 weeks old.